2012
DOI: 10.1095/biolreprod.111.098616
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bleomycin, Etoposide, and Cis-Platinum Alters Rat Sperm Chromatin Integrity and Sperm Head Protein Profile1

Abstract: Testicular cancer, currently the most common cancer affecting men of reproductive age, is one of the most curable malignancies due to the progress made in the early diagnosis and effective treatment of this disease. The coadministration of bleomycin, etoposide, and cis-platinum (BEP) has brought the 5-yr survival rate of testis cancer patients to over 90%. However, this treatment results in reproductive chemotoxic effects. We assessed the effect of BEP treatment on sperm chromatin integrity and sperm head prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Spermadine, the product of SRM, is important in fetal development, stages of spermatogenesis and steroidogenesis (Lefevre et al 2011). HSP90B1 was recently associated with alterations in sperm chromatin integrity following exposure to chemotherapeutic agents (Maselli et al 2012) and found to be predictive of small clusters. Interestingly, while DPYL2 was not correlated with the formation of large Leydig cell clusters, it was predictive of these clusters.…”
Section: Biomarkers Of Dysgenesis In Fetal Rat Testismentioning
confidence: 99%
“…Spermadine, the product of SRM, is important in fetal development, stages of spermatogenesis and steroidogenesis (Lefevre et al 2011). HSP90B1 was recently associated with alterations in sperm chromatin integrity following exposure to chemotherapeutic agents (Maselli et al 2012) and found to be predictive of small clusters. Interestingly, while DPYL2 was not correlated with the formation of large Leydig cell clusters, it was predictive of these clusters.…”
Section: Biomarkers Of Dysgenesis In Fetal Rat Testismentioning
confidence: 99%
“…Some testis tumors are treated using cisplatin (Koychev et al, 2011). Recent report analyzed the impact of such treatment on the integrity of spermatozoa chromatin in rats (Maselli et al, 2012). As expected, the cisplatin treatment lead to susceptibility of DNA to denaturation and the number of strand breaks were significantly increased in mature sperm.…”
Section: Epigenetic and Testicular Cancersmentioning
confidence: 99%
“…However, this balance can readily be broken by the chemicals like the CP, that disrupts the prooxidant-antioxidant balance, leading to cellular dysfunction [20] . Also, the CP can induce free radical toxic stress and spermatic DNA damage [21,22] .…”
Section: Introductionmentioning
confidence: 99%